A Novel Heat Shock Element (HSE) in Entamoeba histolytica that Regulates the Transcriptional Activation of the EhPgp5 Gene in the Presence of Emetine Drug - Nieto, Alma; Pérez Ishiwara, David G.; Orozco, Esther; Sánchez Monroy, Virginia; Gómez García, Consuelo (Frontiers in Cellular and Infection Microbiology, 2017)
ABSTRACT Transcriptional regulation of the multidrug resistance EhPgp5 gene in Entamoeba histolytica is induced by emetine stress. EhPgp5 overexpression alters the chloride-dependent currents that cause trophozoite swelling, diminishing induced programmed cell death (PCD) susceptibility. In contrast, antisense inhibition of P-glycoprotein (PGP) expression produces synchronous death of trophozoites and the enhancement of the biochemical and morphological characteristics of PCD induced by G418. Transcriptional gene regulation analysis identified a 59 bp region at position -170 to -111 bp promoter as putative emetine response elements (EREs). However, insights into transcription factors controlling EhPgp5 gene transcription are missing; to fill this knowledge gap, we used deletion studies and transient CAT activity assays. Our findings suggested an activating motif (-151 to -136 bp) that corresponds to a heat shock element (HSE). Gel-shift assays, UV-crosslinking, binding protein purification and western blotting assays revealed proteins of 94, 66, 62, and 51 kDa binding to the EhPgp5 HSE that could be heat shock-like transcription factors that regulate the transcriptional activation of the EhPgp5 gene in the presence of emetine drug.